The criticality of clean energy and ICT invesment in achieving environmental sustainability in the EU member states - Lunku, Hassan Swedy (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
Defining and designing appropriate energy, economic and environmental policies that help minimize global carbon emissions remains a top priority for all governmental and non-governmental environmental organizations worldwide. In this digital age, the researcher has paid particular attention to his increasing use of ICT and its relevance to economic and environmental aspects. This paper addresses the sustainability challenges and energy security issues posed by rising energy demand, researchers and policymakers have identified clean future energy alternatives using the most recent data to provide important information for policymakers. The study focused on the key components of ICT investments to promote clean energy (renewables and nuclear) and carbon neutrality in a particular economy with the use of the most robust econometric panel data method for the latest available data sets to obtain reliable and efficient estimates. The study findings demonstrate that using renewable energy can help the EU achieve energy security while reducing greenhouse gas emissions. However, renewable energy deployment is still not substantial enough to mitigate environmental pollution in the presence of significant ICT investment in the EU member states.